2001
DOI: 10.1525/si.2001.24.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Legitimating the First Tattoo: Moral Passage through Informal Interaction

Abstract: Once considered low class or dangerous symbols, tattoos began to be defined as hip, trendy, and glamorous in the 1990s. Using the increasing popularity of tattoos among nineties youth as an example of moral passage, this article examines some of the interpretive processes at work in the destigmatization of deviance. Whereas researchers have positioned political action or population shifts as the main forces influencing moral passage, this article posits a new route toward social change. It builds on participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
115
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(118 citation statements)
references
References 47 publications
1
115
0
2
Order By: Relevance
“…The view of tattoos as a deviant activity is influenced by the belief that they are a deliberate affront to social standards or indicate an affiliation with a deviant activity or group (Bell 1999;DeMello 2000;Irwin 2001Irwin , 2003Vail 1999). Body modification is linked with deviant and risky behavior and mental illness (Atkinson 2004;DeMello 2000;Kosut 2006), and this is largely due to an over-focus on college student, juvenile delinquent, inpatient, and adjudicated populations where deviance and mental illness are more prevalent (Atkinson 2004;Struppy, Armstrong, and Casals-Ariet 1998).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The view of tattoos as a deviant activity is influenced by the belief that they are a deliberate affront to social standards or indicate an affiliation with a deviant activity or group (Bell 1999;DeMello 2000;Irwin 2001Irwin , 2003Vail 1999). Body modification is linked with deviant and risky behavior and mental illness (Atkinson 2004;DeMello 2000;Kosut 2006), and this is largely due to an over-focus on college student, juvenile delinquent, inpatient, and adjudicated populations where deviance and mental illness are more prevalent (Atkinson 2004;Struppy, Armstrong, and Casals-Ariet 1998).…”
mentioning
confidence: 99%
“…Body modification is linked with deviant and risky behavior and mental illness (Atkinson 2004;DeMello 2000;Kosut 2006), and this is largely due to an over-focus on college student, juvenile delinquent, inpatient, and adjudicated populations where deviance and mental illness are more prevalent (Atkinson 2004;Struppy, Armstrong, and Casals-Ariet 1998). For women, tattooing: (a) is a violation of basic standards of appearance, (b) is considered less feminine, and (c) may result in women being perceived as displaying more negative personality characteristics (Irwin 2001(Irwin , 2003Rosenhoeft et al 2008). Even so, recent research supports that women are being tattooed at nearly equivalent levels to men, so it no longer has a mostly masculine appeal (Adams 2012).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have also found that piercing and tattooing may represent a person's attempt to individuate him-or herself from the larger society. The body can be the ideal site for this highly personal act (Claes et al, 2005;Irwin, 2001;Velliquette & Murray, 2002).…”
mentioning
confidence: 99%